The nature of delayed dream incorporation (‘dream-lag effect’): Personally significant events persist, but not major daily activities or concerns - Mark Blagrove (Journal of Sleep Research, 2019)
Incorporation of details from waking life events into rapid eye movement (REM) sleep dreams has been found to be highest on the 2 nights after, and then 5–7 nights after, the event. These are termed, respectively, the day‐residue and dream‐lag effects. This study is the first to categorize types of waking life experiences and compare their incorporation into dreams across multiple successive nights. Thirty‐eight participants completed a daily diary each evening and a dream diary each morning for 14 days. In the daily diary, three categories of experiences were reported: major daily activities (MDAs), personally significant events (PSEs) and major concerns (MCs). After the 14‐day period each participant identified the correspondence between items in their daily diaries and subsequent dream reports. The day‐residue and dream‐lag effects were found for the incorporation of PSEs into dreams (effect sizes of .33 and .27, respectively), but only for participants (n = 19) who had a below‐median total number of correspondences between daily diary items and dream reports (termed “low‐incorporators” as opposed to “high‐incorporators”). Neither the day‐residue or dream‐lag effects were found for MDAs or MCs. This U‐shaped timescale of incorporation of events from daily life into dreams has been proposed to reflect REM sleep‐dependent memory consolidation, possibly related to emotional memory processing. This study had a larger sample size of dreams than any dream‐lag study hitherto with trained participants. Coupled with previous successful replications, there is thus substantial evidence supporting the dream‐lag effect and further explorations of its mechanism, including its neural underpinnings, are warranted.